DIGITALISASI PEMASARAN DAN REBRANDING PRODUK UMKM LEZATE JAMUR GUNUNGPATI SEMARANG MELALUI PELATIHAN, PENDAMPINGAN DAN PENERAPAN TEKNOLOGI TEPAT GUNA - Herny Februariyanti; Teguh Khristianto; Esteria Priyanti (Jurnal Abdi Insani, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in economic development. This Community Partnership Program (CPP) aims to enhance the digital marketing capacity and brand strengthening of Lezate Jamur, an MSME located in Gunungpati, Semarang, through training, mentoring, and the application of appropriate technology. The program methods include partner needs identification, instructional material design, digital marketing training (branding, product photography, copywriting, and marketplace management), packaging and label redesign, implementation of a vacuum sealer to improve product quality, as well as operational assistance and evaluation. The evaluation was conducted using achievement checklists, pre–post understanding assessments, production logs, and digital account analytics. The results indicate that the partner was able to activate and manage digital marketing channels (Instagram, TikTok, and marketplaces), develop a more consistent brand identity (logo, color scheme, and value proposition), and improve packaging from plain plastic to informative labeled packaging. The implementation of a vacuum sealer helped maintain product cleanliness and neatness, making the products more suitable for online marketing. In terms of production, daily capacity increased from approximately 5–7 kg to 10 kg per day (an increase of about 30–40%) in line with improved workflow and rising demand. Overall, this program strengthened the MSME’s readiness to adapt to online shopping patterns and expand market reach. Future efforts should include periodic monitoring of digital channel performance and structured measurement of packaging costs, shelf life, and consumer perceptions.